Hyphessobrycon lucenorum (Characiformes: Characidae), a new species from the rio Madeira basin, Rondônia State, Brazil - Ohara, Willian M.; Lima, Flávio. C.t. (Zootaxa, 2015)
A new species of characid is described from the upper rio Machado, a tributary of the rio Madeira basin, Rondônia, Brazil. Hyphessobrycon lucenorum can be distinguished from all congeners by the unique combination of the presence of a conspicuous rounded humeral blotch and a broad and diffuse longitudinal stripe. The new species is included within the Hyphessobrycon agulha group. The high number of endemic species of fishes occurring in the headwater tributaries of three river systems (rio Madeira, rio Tapajós, and rio Paraguai) draining the watershed defined by the Chapada dos Parecis is discussed.